2017
DOI: 10.1016/j.talanta.2017.03.103
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis tandem mass spectrometry determination of glutamic acid and homocysteine’s metabolites: Potential biomarkers of amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that affects both lower and upper motor neurons, leading to muscle atrophy, paralysis, and death caused by respiratory failure or infectious complications. Altered levels of homocysteine, cysteine, methionine, and glutamic acid have been observed in plasma of ALS patients. In this context, a method for determination of these potential biomarkers in plasma by capillary electrophoresis tandem mass spectrometry (CE-MS/MS) is proposed herein. Sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 33 publications
2
18
0
1
Order By: Relevance
“…Biomarker identification is performed in different biological fluids, blood being one of the most promising amongst them. In recent studies, metabolites and especially amino acids were identified as biomarkers in blood for amyotrophic lateral sclerosis , chronic kidney disease (CKD) , major depressive disorder , onchocercias infection , osteoporosis , Parkinson's disease , pancreatic cancer , urinary tract symptoms and metabolic syndrome in postmenopausal women by CZE‐MS. For identification and accurate quantification of biomarkers for inborn errors of metabolism from dried blood spots, DiBattista et al.…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Biomarker identification is performed in different biological fluids, blood being one of the most promising amongst them. In recent studies, metabolites and especially amino acids were identified as biomarkers in blood for amyotrophic lateral sclerosis , chronic kidney disease (CKD) , major depressive disorder , onchocercias infection , osteoporosis , Parkinson's disease , pancreatic cancer , urinary tract symptoms and metabolic syndrome in postmenopausal women by CZE‐MS. For identification and accurate quantification of biomarkers for inborn errors of metabolism from dried blood spots, DiBattista et al.…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…The separation occurred in less than 25 min using a 5 M acetic acid migration buffer with estimated LODs ranging from 35 nM (Hcy) to 268 nM (Glu). Analyses of plasma from patient with amyotrophic lateral sclerosis were described, demonstrating the potential of glutamic acid and homocysteine metabolites as biomarkers .…”
Section: Biomedical Analysesmentioning
confidence: 99%
“…A study of blood plasma from ALS patients and healthy controls, using MS-targeted metabolomics, identified significantly higher levels of glutamic acid and homocysteine in the plasma of these patients [ 17 , 83 ]. Although those molecules are potential biomarkers for ALS, further studies are necessary to confirm their mechanisms for ALS physiology [ 83 ].…”
Section: Metabolites In Specific Neurological Diseasesmentioning
confidence: 99%
“…In addition, it is also possible to observe the involvement of harmful oxidative processes, with the potential to affect membranes, as has already been proposed for Lysophosphatidic acid C18: 2 in patients with AD [ 71 ]. Furthermore, carnitine and the related metabolite acetylcarnitine, an intermediary of fatty acid oxidation, were found in studies on AD, ALS, MS, and stroke and related to impairment mitochondrial and energy metabolisms and fatty acids transport during the catabolism of lipids [ 9 , 68 , 83 , 109 ]. Because of the acetyl group, the acetylcarnitine can cross the blood–brain barrier more easily and is the preferred form in the central nervous system [ 9 ].…”
Section: Metabolites In Specific Neurological Diseasesmentioning
confidence: 99%